Guns, germs, and steel [videorecording (DVD)] - Lambert, Tim; Harrison, Cassian; Diamond, Jared M. (National Geographic, 2005)
An epic detective story that offers a gripping expose on why the world is so unequal. Professor Jared Diamond traveled the globe for over 30 years trying to answer this question. Based on the Pulitzer Prize-winning book. Why did Eurasians conquer, displace, or decimate Native Americans, Australians, and Africans, instead of the reverse? Diamond dismantles racially based theories of human history by revealing the environmental factors actually responsible for history's broadest patterns.